Awareness of CPR among the family members of the patients visiting the hospital. A cross-sectional survey study - Shrestha, Gentle Sunder; Bhattarai, Amit Sharma; Shrestha, Manjit; Subba, Rusy; Kafle, Riju; Bhattarai, Shraddha; Shrestha, Bibeka; Singh, Shreejana; Pradhan, Rojika (Bangladesh Critical Care Journal, 2022)
Background: Cardiac arrest is a common cause of morbidity and mortality. In out-of-hospital setting, early recognition of cardiac arrest and bystander-initiated cardiopulmonary resuscitation (CPR) improves both the chance of survival and quality of life. Objectives: The study aimed to explore awareness regarding cardiac arrest and knowledge of CPR among visitors of patients at a tertiary level hospital. Design: Cross sectional study. Method: The validated and tested self-administered questionnaire were distributed among 394 visitors of the patients admitted at Alka Hospital Pvt. Ltd, Lalitpur, Nepal. Results: Our study demonstrated that 221 (56.1%) of the respondents have knowledge regarding CPR and 201 (51.0%) of respondents have awareness about cardiac arrest through medias (37.8%) like movies and television. We found a significant difference among age group, occupation and geographical location regarding awareness of cardiac arrest. People with greater age and education knew better about cardiac arrest. There was, however, no significant difference amongst groups regarding knowledge of CPR. Very little respondents have heard about automated external defibrillators (AED). Conclusions: There is paucity in knowledge of cardiac arrest and CPR among respondents. Similarly, there is a general lack of knowledge regarding AED. Effective programs to raise the awareness of cardiac arrest and knowledge of CPR needs to be undertaken at the community level to reinforce bystander-initiated CPR and potentially save lives in the scenario of out-of-hospital cardiac arrest. Bangladesh Crit Care J September 2022; 10(2): 82-87